2015
DOI: 10.3928/01913913-20150526-01
|View full text |Cite
|
Sign up to set email alerts
|

Macular Thickness in Highly Myopic Children Aged 3 to 7 Years

Abstract: Anatomic changes in the retina occur even in young children with high myopia. Macular thickness characteristics of highly myopic children may influence the interpretation of data obtained with OCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 28 publications
2
11
5
Order By: Relevance
“…To date, the relationship between RT and progression of myopia in children remains elusive. Some studies demonstrated that foveal RT was significantly decreased in highly myopic subjects [40], and some studies found that increasing axial myopia was associated with increased foveal RT and reduced parafoveal and perifoveal RT [37], or quadrant-specific RT [41,42], while others reported the absence of any association [43]. The current study found no significant correlation between baseline RT and baseline AL or SE.…”
Section: Discussioncontrasting
confidence: 65%
“…To date, the relationship between RT and progression of myopia in children remains elusive. Some studies demonstrated that foveal RT was significantly decreased in highly myopic subjects [40], and some studies found that increasing axial myopia was associated with increased foveal RT and reduced parafoveal and perifoveal RT [37], or quadrant-specific RT [41,42], while others reported the absence of any association [43]. The current study found no significant correlation between baseline RT and baseline AL or SE.…”
Section: Discussioncontrasting
confidence: 65%
“…Previous investigations mainly explored the effect of myopia on macular thickness, with variable results. 28,29,30,31,32 Although these studies used various methods to measure macular thickness, they generally found that macular thinning was associated with increasing myopia, and that it mainly occurred in the inner and outer maculae rather than at the central macula. 28,32 It has been reported in several studies that the central macular thickness becomes thicker with increasing myopia 28,32 or that it did not change.…”
Section: Discussionmentioning
confidence: 99%
“…This was similar to the study of Choi and Lee [ 25 ]. Ziylan et al [ 26 ] compared the macular thicknesses of highly myopic children with healthy controls and found that foveal thickness was significantly greater in the high myopia group and parafoveal thicknesses of the inner and outer circles were significantly thinner in the high myopia group. However, in the studies of Barrio-Barrio et al [ 6 ] and Al-Haddad et al [ 27 ], no correlation between macular thickness and refraction was reported.…”
Section: Discussionmentioning
confidence: 99%